Spatiotemporal autoregressive model for Malaysian housing market analysis [electronic resource] - 513019 Nurul Hana Adi Maimun (2011)
Thesis (Sarjana Sains (Harta Tanah)) - Universiti Teknologi Malaysia, 2011